Articulating urban change in Southern Europe: Gentrification, touristification and financialisation in Mouraria, Lisbon. (April 2021) - Tulumello, Simone; Allegretti, Giovanni
The global or planetary reach of gentrification has become a mainstream in critical urban studies. Yet, the 'travels' of a concept originated in specific places and times have often brought about a loss of explanatory and strategic power. In this article, we argue that another concept, that of articulation developed by Laclau and Mouffe, is particularly adequate to help gentrification, touristification and financialisation to travel among places and levels of abstraction. In order to make this argument, we focus on Southern Europe, whose cities had long been considered scarcely gentrifiable and where, more recently, critical urban scholarship has made large use of gentrification, touristification and financialisation to explain the impacts of crisis, austerity and afterwards economic rebound driven by real estate and tourism. We explore from a multi-scalar perspective the trajectory of Mouraria, a historical neighbourhood in Lisbon – and particularly the dimensions of housing and local politics. We show how Mouraria, during the last decade, shifted from being a 'deviant' case – capable of taking advantage of neoliberal regeneration policies in order to keep its social diversity and most of its long-term residents – towards one 'paradigmatic' of urbanisation-as-accumulation and contentious urban politics. We explain this shift by focusing on its multi-scalar determinants, concluding that present urban change in many Southern European cities should be understood as the articulation of various processes, which include gentrification, touristification and financialisation.